Nicotinic acid has anti-atherogenic and anti-inflammatory properties on advanced atheroscleroticlesions independent of its lipid-modifying capabilities - Holzhäuser, Eva; Albrecht, Claudia; Zhou, Qianxing; Buttler, Annette; Preusch, Michael; Blessing, Erwin; Katus, Hugo; Bea, Florian (Journal of cardiovascular pharmacology, 2011)
Inflammation contributes to atherosclerotic plaque initiation and progression. Recent studies suggest that nicotinic acid has anti-inflammatory effects independent of its lipid-modifying capabilities. We assessed the hypothesis that administration of nicotinic acid to older apolipoprotein E (apoE)-deficient mice with established lesions will reduce lesion size and plaque inflammation independent of its lipid-modifying effects. Therefore nicotinic acid was administered to 27-week-old apo E-deficient mice exhibiting advanced atherosclerotic lesions within the innominate artery. After 27 weeks of treatment both animal groups had no significant changes in plasma lipid levels. Mice treated with nicotinic acid (n = 22) demonstrated a 30% reduction in total lesion area compared with controls (n = 20). Furthermore, they revealed a more stable plaque composition with an increase in fibrous cap thickness and a reduction in the size of the necrotic core. Immunohistochemistry demonstrated a reduced accumulation of macrophages and a reduced expression of vascular cell adhesion molecule-1 and tissue factor. Additionally, administration of nicotinic acid significantly reduced tumor necrosis factor alpha expression in the thoracic aorta as demonstrated by real-time PCR. In conclusion, these data suggest that long-term administration of nicotinic acid has anti-atherogenic and anti-inflammatory properties on advanced atherosclerotic lesions, which are independent of its lipid-modifying actions.
Gesehen am 29.06.2022